Late cretaceous continental and marine vertebrate assemblages from the Laño quarry (Basque-Cantabrian Region, Iberian Peninsula): an update - Pereda-Suberbiol, X.; Corral, J.C.; Astibia, H.; Badiola, A.; Bardet, N.; Berreteaga, A.; Buffetaut, E.; Buscalioni, A.D.; Cappetta, H.; Cavin, L.; Díez Díaz, V.; Gheerbrant, E.; et al. (Journal of Iberian Geology, 2015)
The vertebrate-bearing beds of the Laño quarry (Condado de Treviño) are among the most relevant sites from the Late Cretaceous of Europe. Geologically, Laño and the adjacent region are set on the southern limb of the South-Cantabrian Synclinorium (SE Basque-Cantabrian Region, northern Iberian Peninsula). The Laño sites were discovered in 1984; thousands of bones and teeth, including microfossils, have been collected during the prospection in the field and excavation campaigns. The vertebrate remains occur at two different stratigraphic horizons within a continental to shallow marine succession of Late Campanian-Maastrichtian age. The lower horizon contains the Laño 1 and Laño 2 sites, whereas the upper horizon contains the Albaina site. In the Laño sites, three fossiliferous beds (called L1A, L1B and L2) are known within an alluvial system composed mainly of fluvial sands and silts. The sedimentary structures are consistent with channel areas within an extensive braided river system. Based mainly on stratigraphic correlations, the fluvial beds of Laño are regarded as Late Campanian to Early Maastrichtian in age. These deposits have yielded a very diverse vertebrate assemblage, which consists of nearly 40 species, including actinopterygians, lissamphibians, lepidosaurs, turtles, crocodyliforms, dinosaurs, pterosaurs, and mammals. Seven genera and ten species have been erected to date in Laño. With reference to the marine vertebrate association of Albaina, it consists of at least 37 species, including sharks and rays, actinopterygians, mosasaurids, and plesiosaurs. Two genera and species of rhinobatoids (family indet.) and two new species of rhinobatids have been erected in Albaina. The fossil association indicates a Late (but not latest) Maastrichtian age. Recently, isolated turtle and dinosaur fossils have been discovered in the sublittoral beds of Albaina. The Laño quarry is one of the most noteworthy Campanian-Maastrichtian vertebrate localities of Europe by its taxonomic diversity, and provides useful information about the composition and affinities of both continental and marine vertebrate faunas from the latest Cretaceous of southwestern Europe.